ASME 2011 Internal Combustion Engine Division Fall Technical Conference 2011
DOI: 10.1115/icef2011-60141
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inlet Air Temperature on Auto-Ignition of Fuels With Different Cetane Number and Volatility

Abstract: This paper investigates the effect of air inlet temperature on the auto-ignition of fuels that have different CN and volatility in a single cylinder diesel engine. The inlet air temperature is varied over a range of 30°C to 110°C. The fuels used are ultra-low-sulfur-diesel (ULSD), JP-8 (two blends with CN 44.1 & 31) and F-T SPK. Detailed analysis is made of the rate of heat release during the ignition delay period, to determine the effect of fuel volatility and CN on the auto-ignition process. A STAR-CD CF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…All research ers agree on the start of injection (SOI) as the start of ID. However, several criteria have been used to define the end of ID or the start of combustion (SOC) [24][25][26][27][28][29][30][31][32]. In the current investiga tion, the definition of ID specified in ASTM D6890 [2] was used as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…All research ers agree on the start of injection (SOI) as the start of ID. However, several criteria have been used to define the end of ID or the start of combustion (SOC) [24][25][26][27][28][29][30][31][32]. In the current investiga tion, the definition of ID specified in ASTM D6890 [2] was used as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…53,54 Lower CN fuels generally gave a larger fraction of premixed burn. 136 Due to the higher volatility of kerosene, a near-stoichiometric fuel–air mixture was formed and NO x emissions increased significantly. 42,53 However, by using EGR and optimized injection strategies, NO x and soot trade-off was proven to be possible with minimal loss in efficiency.…”
Section: Experimental Investigations Of Kerosene Combustion and Emissions In Dici Enginesmentioning
confidence: 99%
“…[120][121][122][123][124][125][126] It should be noted that studies done recently on kerosene combustion were predominantly done using DICI engines. 6,42,53,54,[127][128][129][130][131][132][133][134][135][136] From DICI engine experiments, it was observed that kerosene had a longer ignition delay period than diesel even though kerosene had a lower viscosity and better vaporization characteristic. 6,53,54 Under high EGR rates, the difference between diesel's and kerosene's ignition delay became much more obvious.…”
Section: Kerosene Combustion In Non-optical Enginesmentioning
confidence: 99%
See 1 more Smart Citation
“…All researchers agree on the start of injection (SOI) as the start of ID. However, several criteria have been used to define the end of ID or the start of combustion (SOC) [24][25][26][27][28][29][30][31][32].…”
Section: Methodsmentioning
confidence: 99%